THE IMPACT OF TAX AGGRESSIVENESS ON FIRM VALUE AND AUDIT QUALITY - Arfandi Arfandi; Sri Sundari; Mediaty Mediaty (Adisam Publisher, 2026)
This study aims to examine in depth the impact of tax aggressiveness on firm value and audit quality using a literature review method. In an increasingly competitive and complex business environment, companies often employ tax aggressive practices as a strategy to minimize their tax burden and increase profitability. The method used in this study is a systematic literature review, identifying, categorizing, and analyzing findings from various relevant scientific articles. The results indicate that tax aggressiveness has diverse impacts on firm value. On the one hand, tax aggressiveness can increase firm value in the short term by increasing after-tax profits. This study confirms that the interaction between tax aggressiveness, firm value, and audit quality is a crucial aspect of modern corporate governance.